Perancangan dan Implementasi Sistem Pemantauan Kualitas Udara berbasis IoT menggunakan Wemos D1 Mini dan Android - Prakoso, Alvian Dafa; Wellem, Theophilus (Forum Kerjasama Pendidikan Tinggi, 2022)
Internet-of-Things (IoT)-based monitoring and control systems have been widely used in daily life, for example, in smart cities, smart homes (or home automation), and intelligent transportation applications. One example of the application of IoT in smart cities and smart homes is the air quality monitoring system. Monitoring air quality, both indoors and outdoors, is essential for health. This study aims to design and implement an IoT-based air quality monitoring system. The hardware in this system uses the Wemos D1 Mini board, the MQ-9 gas sensor to measure carbon monoxide (CO) gas levels, and the MQ-135 gas sensor to measure carbon dioxide (CO2) gas levels. An Android-based application is also implemented to access and display the results of air quality measurements by the system stored in the cloud database (Firebase). System testing is carried out using smoke from burning paper at varying distances from the sensors. The system test results show that the implemented system can measure CO gas levels in the room from 7 ppm to 38 ppm. The measurement results for CO2 gas levels in the room are between 200 ppm to 1000 ppm.